PENGARUH MOTIVASI BELAJAR DAN KONSEP DIRI TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM PESERTA DIDIK DI PONDOK PESANTRENAL-KAUTSAR TEBO - Sakinah, Siti; Ahmad Ridwan; Muhamad Taridi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine The Influence of Learning Motivation and Self-Concept on Students’ Achievement in Islamic Religious Education at Al-Kautsar Islamic Boarding School TeboThis research employed a quantitative approach with a correlational design. Data were collected through questionnaires, documentation, and observation. The population consisted of 90 students, and total sampling technique was applied. Data analysis was conducted using multiple linear regression, t-test, F-test, and coefficient of determination with the help of SPSS. The results revealed that: (1) learning motivation has a positive and significant effect on students’ achievement in Islamic Religious Education, (2) self-concept has a positive and significant effect on students’ achievement, and (3) learning motivation and self-concept simultaneously have a significant effect with a contribution of 12.4%. In conclusion, learning motivation and self-concept are important factors in improving students’ academic achievement. The implication of this study highlights the importance of enhancing learning motivation and developing positive self-concept through effective teaching strategies, guidance, and supportive educational environments. Keywords: Learning Motivation, Self-Concept, Learning Achievement, Islamic Religious Education